The Strict Liability of State Suppliers in the Presentation of False Documentation or Inaccurate Affidavit - Martínez Zamora, Marco Antonio (2015)
The present paper pretends to open the debate about the limits of responsibility of State suppliers on the presentation of false or inexact documentation on the selection procedures as a participator on the frame of the public procurement law, considering that the burden of proof has been translated to the governed, punishing in a more severe way the infringement to the due of veracity on the documentation that is provided by suppliers to public entities.